1988
DOI: 10.1002/jmv.1890250113
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of human rotavirus polypeptides in cell culture

Abstract: The replication strategy of a human serotype 1 rotavirus, adapted to rapid growth in CV-1 cells, was investigated. A single cycle growth curve revealed eclipse and latent periods of 3 and 4 hours, respectively. Although the extent of reduction of host cell protein synthesis was directly related to the multiplicity of infection of the virus, incorporation of actinomycin D and excess NaCl into the medium resulted in significant reduction in host cell background and enabled observation of viral polypeptides as ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…No translation elongation factors were found to be modulated in this analysis. It has been shown that rotavirus infection mediates a reduction of cellular protein synthesis, favoring translation of viral proteins (25,45). If the upregulation of the translation associated genes seen here is correlated with an upregulation of the corresponding host proteins, one might speculate that rotavirus induces an upregulation of the protein translation machinery of the cell and uses this machinery for the synthesis of its own proteins, while simultaneously blocking host cellular protein synthesis.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…No translation elongation factors were found to be modulated in this analysis. It has been shown that rotavirus infection mediates a reduction of cellular protein synthesis, favoring translation of viral proteins (25,45). If the upregulation of the translation associated genes seen here is correlated with an upregulation of the corresponding host proteins, one might speculate that rotavirus induces an upregulation of the protein translation machinery of the cell and uses this machinery for the synthesis of its own proteins, while simultaneously blocking host cellular protein synthesis.…”
Section: Discussionmentioning
confidence: 80%
“…Viruses cause a variety of responses in infected cells, including changes in gene and protein expression, interferon (IFN) response, regulation of cell surface molecules, etc. A reduction in cellular protein synthesis has been reported in rotavirus-infected cells (25). Changes in intracellular Ca 2ϩ concentration (associated with virus maturation and proposed to be related to cell death) (41), alterations in the organization of the cell cytoskeleton (5,28), structural and functional alterations in the tight junctions (43), and cellular lysis (15) have also been described following rotavirus infection.…”
mentioning
confidence: 99%
“…Accepting that the binding of phalloidin was indeed specific for F-actin, the FITC-phalloidin stained actin was found to be mainly concentrated in the hyphal tips in which it formed a uniform cap lying essentially in the cortical zone of the hyphae (Fig. 5A,B) be also found in the hyphae of Saprolegnia ferax [4,27]. The subapical structures of actin were visualized as dots (Fig.…”
Section: Intrahyphal Distribution Of Actinmentioning
confidence: 94%
“…Emergence of germ tubes from Neurospora conidia and of Mueor sporangiophores were prevented by cytochalasin B and A, respectively [9,36]. Even though actin microfilaments would not play a direct role in saltatory organelle motility [4], they would be involved in the inception and maintenance of polarized growth of hyphae through control of directional trafficking of wall-precursor-containing vesicles to their elongating tips.…”
Section: Intrahyphal Distribution Of Actinmentioning
confidence: 99%
See 1 more Smart Citation